Spherical and needle shaped magnetic nanoparticles for friction and magnetic stimulated transformation of microorganisms - Mendes, Gabriel Pinto (2021)
Supplementary material related to this article can be found online at https://doi.org/10.1016/j.nanoso.2021.100732.